Growing Cassava (Manihot esculenta) in Mato Grosso, Brazil: Genetic Diversity Conservation in Small-Scale Agriculture - Carrasco, N. F.; Oler, J. R. L. [UNESP]; Marchetti, F. F. [UNESP]; Carniello, M. A.; Amorozo, M. C. M. [UNESP]; Valle, T. L.; Veasey, E. A. (Springer, 2016)
Growing Cassava ( Manihot esculenta ) in Mato Grosso, Brazil: Genetic Diversity Conservation in Small-Scale Agriculture. Cassava (Manihot esculenta Crantz) is a tropical species that stands out as a food source for developing countries. Within an ethnobotanical and socioeconomic context, this study aimed to compare the level of genetic diversity of cassava maintained by small farmers in three municipalities of the Cuiaba Lowland in the state of Mato Grosso, Brazil: Caceres, Porto Estrela, and Santo Antnio do Leverger. This region, which is included in the center of origin of cassava, is currently undergoing profound socioeconomic changes that can have negative impacts in the on farm conservation of cassava agrobiodiversity. We characterized 211 genotypes collected in 40 households in 10 communities, using 14 microsatellite loci. High levels for the observed (H (O) = 0.587) and expected (H (E) = 0.525) heterozygosities were found, whereas most of the genetic diversity was concentrated within communities (92%). A genetic differentiation was found between the municipality of Santo Antnio do Leverger and the municipalities of Caceres and Porto Estrela, not only due to a higher geographic distance among them, but also due to soil, climatic, and cultural factors. A different number of local varieties was observed in each municipality, while the number of unique varieties in each municipality was high, 83%, 84%, and 61%, respectively, representing an important aspect for the in situ conservation of this crop. Although local names provided by farmers were phenotypically coherent, intravarietal variability among local varieties sharing the same name was high (97%). Santo Antnio do Leverger was considered as a priority area for in situ conservation. Nevertheless, in view of the decline in local traditional agriculture systems and socioeconomic transformations in this region, public policies providing support and incentives to farmers are necessary.
Keywords: Genetic structure; local varieties; Manihot esculenta; microsatellites; traditional agriculture; ethnobotany